Soil and water conservation for climate-resilient agriculture - Kizito, Fred; Chikowo, Regis; Kimaro, Anthony A.; Swai, Elirehema (CAB International, 2022)
This chapter describes soil and water conservation measures for climate-resilient agriculture. It presents three interventions that can be used separately or in combination, depending on the context of the region: (1) integrating strips of forage grasses and legumes; (2) rainwater harvesting through tied ridges and ripping techniques; (3) constructing banks and ditches as part of an agroforestry system. The description of each technology, its benefits and application are discussed.